Which programme do you prefer? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Rural radio stations, like any other, need to know the impact that their programmes are having on their listeners. How can this be measured when the service of specialised institutes are beyond reach?This issue has been the theme of a series of six...